A local symmetry result for linear elliptic problems with solutions changing sign - Canuto, B. (2011)
We prove that the only domain Ω such that there exists a solution to the following problem Δu+ω2u=-1 in Ω, u=0 on δΩ, and 1|δΩ|∫δΩδ nu=c, for a given constant c, is the unit ball B1, if we assume that Ω lies in an appropriate class of Lipschitz domains. © 2011 Elsevier Masson SAS.